KONSEP KETUHANAN ISLAM JAWA DIENG (Studi Terhadap Aliran Tunggul Sabda Amungraga) - Bani Sudardi (IBDA` : Jurnal Kajian Islam dan Budaya, 2013)
This research reveals the teaching of a religious sect in Diengwhich focuses on theological concept. Clifford Geerts' concept is used todiscuss the social and art area. There are some results on this research; abelief to the invisible nature, the Islamic teaching from Sunan Kalijaga,Mataram teaching with some enculturation, and a statement that Allah isthe only one who is worth to be worshipped.